Research on Sustainable Development from the Perspectives of ecosystem service value and Urbanization: A Case Study of Guangxi - Zhou Lanhui; Xu Jinxuan; Qu Hongjiao (E3S Web of Conferences)
Research on the coupling of ecosystem service values (ESV) and urbanization is essential for maintaining ecosystem stability and achieving sustainable development goals (SDGs). This study separately assessed the ESV and urbanization in Guangxi from 2000 to 2020, uncovering their spatiotemporal distribution differences over the years. A coupled coordination model (CCD) is developed to analyze the coupled coordination relationship between the two to fill the gap in the current research. The main results are as follows: (1) From 2000 to 2020, the ESV of Guangxi shows a slightly decreasing trend and a dispersed spatial distribution characteristic of low in the middle and high in the surrounding area. (2) The urbanization index of Guangxi shows a continuous upward trend. In terms of spatial changes, the degree of cities in the central part of the country is higher, and the degree of urbanization around it is lower. (3) The overall trend of the coupling coordination degree between ESV and urbanization shows an increasing trend, indicating a good level of coordination between urban development and environmental protection in Guangxi. The higher degree of coordination in cities with better economic development in the central part of the country. This study provides a new perspective for understanding the ESV and its relationship with urbanization, and provides an important reference for sustainable management of ecosystems and ecological conservation policy formulation.